2021
DOI: 10.1371/journal.pone.0245105
|View full text |Cite
|
Sign up to set email alerts
|

Establishing defined daily doses (DDDs) for antimicrobial agents used in pigs, cattle and poultry in Japan and comparing them with European DDD values

Abstract: Monitoring of antimicrobial use is essential in the management of the development and selection of antimicrobial resistance. A variety of indicators has become available to monitor antimicrobial use in human and animal medicine. One of them is an indicator based on defined daily dose (DDD). By using the number of DDDs administered and normalising it by the population at risk of being treated over a defined period, one can estimate the number of treatment days with antimicrobial agents in a population. For vete… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Our results also revealed that antimicrobial use monitoring systems at farm level will provide similar results in identification of heavy antimicrobial users regardless of whether the Japanese or European DDD value is used (Fig 3 Our results also revealed that the number of DDDjps/PCU was greater than the number of DDDvets/PCU for all 74 farms analyzed in this study (Fig 3). This was attributed to the fact that DDDjp values are lower than DDDvet values for most antimicrobial agents [19]. Also, this study observed that DDDvets did not cover all the antimicrobial agents used in veterinary medicine in null hypothesis for all datasets being declined, correlation was investigated by Spearman's Rho test and found to be significantly correlated (P<0.001).…”
Section: Plos Onementioning
confidence: 82%
See 2 more Smart Citations
“…Our results also revealed that antimicrobial use monitoring systems at farm level will provide similar results in identification of heavy antimicrobial users regardless of whether the Japanese or European DDD value is used (Fig 3 Our results also revealed that the number of DDDjps/PCU was greater than the number of DDDvets/PCU for all 74 farms analyzed in this study (Fig 3). This was attributed to the fact that DDDjp values are lower than DDDvet values for most antimicrobial agents [19]. Also, this study observed that DDDvets did not cover all the antimicrobial agents used in veterinary medicine in null hypothesis for all datasets being declined, correlation was investigated by Spearman's Rho test and found to be significantly correlated (P<0.001).…”
Section: Plos Onementioning
confidence: 82%
“…The DDDvet values were available from the EMA website [17]. The detailed procedure for defining the national doses and all DDDjp values are described in a previous report [19]. To calculate the number of DDDvets for those antimicrobial ingredients for which DDDvet is not available, namely sulfamonomethoxine (for injection), tulathromycin (for injection), dihydrostreptomycin (used in combination product for injection), chlortetracycline(used in combination product for injection), sulfamonomethoxine (for oral administration), streptomycin (used in combination product for oral administration), DDDjp value was used instead.…”
Section: Calculation Of the Number Of Defined Daily Dosesmentioning
confidence: 99%
See 1 more Smart Citation
“…where the DDDjp value of the antimicrobial agent ( a ) administered by route ( r ) was available from the list of Japanese DDDjp values of antimicrobial agents established by Fujimoto et al . [ 12 ]. In preparing this list, the DDDjp values for intramammary products for lactating cows and intrauterine products were assigned by dividing the daily dose per teat by 635 kg (standard weight of dairy cows assigned based on the average weight of dairy cows in 2014 in Japan [ 25 ]).…”
Section: Methodsmentioning
confidence: 99%
“…To establish a monitoring system using an indicator based on daily dosage in Japan, the DDD values (DDDjp) for veterinary antimicrobial agents used in antimicrobial products approved and marketed for use in cattle in Japan have been established recently [ 12 ].…”
mentioning
confidence: 99%